MEMBANGUN KELUARGA BERKETAHANAN SOSIAL DALAM ERA MODERNISASI - Irmayani Irmayani (Sosio Informa, 2007)
As smallest social unit, family share big in following to determine the condition of broader society, covering prosperity of social and harmonious of life bounce him. As place gatherpersonals coexisting in family relationship, quality and pattern between person in the family very determining, do the family pertained harmonious or on the contrary. Besides requiring internal abilities is each family member, do not less important is how the family can stay from all changes that happened around them, change of social, cultural, economy, or politic.Keywords : family, social resilience